Molecular beam epitaxial growth of GaAs/GaNAsBi core–multishell nanowires. (8th November 2021) - Okujima, Masahiro; Yoshikawa, Kohei; Mori, Shota; Yukimune, Mitsuki; Richards, Robert D.; Zhang, Bin; Chen, Weimin M.; Buyanova, Irina A.; Ishikawa, Fumitaro
Abstract: GaAs/GaNAsBi/GaAs core–multishell nanowires were grown using molecular beam epitaxy on Si(111) substrates. The formation of the 20 nm wide GaNAsBi shell with a regular hexagonal structure was observed. The shell is estimated to contain approximately 1.5% N and 2.6% Bi and has a compressive lattice mismatch of less than 0.2% with GaAs layers. The strain mediation by the introduction of both N and Bi suppresses the crystalline deformation, resulting in the clear formation of the GaNAsBi shell. Thus, we obtained room-temperature photoluminescence with the maximum position at approximately 1300 nm from the GaAs/GaNAsBi/GaAs core–multishell nanowires.